Substitutional Application Of Moringa Stem Bark Extract (Moringa oleifera L.) With Basil Stem (Ocimum basilicum L.) On Mortality Of Aedes aegypti Mosquito Larvae - Ati, Vinsensius Manek; Mau, Paula MDS; Meye, Ermelinda D; Amalo, Jeffry (Metamorfosa: Journal of Biological Sciences, 2023)
ABSTRACT          The research was carried out to determine the effect of substitutional of moringa stem bark extract (MB extract) with basil stem extract (BS extract) on mortality, LC 50 and LT 50 of Aedes aegypti larvae. The research was design using completely randomized design (CRD) consist of 6 treatments including control (without MB and BS extracts),  500 mg MB extract, 350 mg MB extract and 150 mg BS extract, 200 mg MB extract and 300 mg BS extract, 50 mg MB extract and 450 mg BS extract, 500 mg BS extract. Each treatment was repeated 4 times. The results of variance analysis indicated that substitution of MB extract with BS extract had a very significant effect (p=0.00) on larval mortality. The highest average mortality was obtained by substitution of 50 mg MB extract with 450 mg BS extract based on Tukey’s test. Probit analysis showed that LC 50 was obtained at a concentration of 35,96 mg/L and LT 50 achieved within 8.58 hours.   Keywords : Aedes aegypti, moringa stem bark, basil stem, mortality, LC 50 , LT 50 .